Characteristics of aluminum-based composites reinforced of Al2O3/B4C by accumulative roll bonding (ARB) - Agus Pramono; Anne Zulfia; Ali Alhamidi; Alfirano Alfirano; Suryana Suryana; Anistasia Milandia (Jurnal Teknika, 2021)
Metalworking technology is currently developing rapidly, especially the processing of metal composite materials. The metalworking process in which ultra-large plastic strains are introduced into the device to create ultra-fine grained metal is a new method for producing high-strength metals. This method is called accumulative roll bonding (ARB). The ideal operating temperature used in the ARB process is the use of dynamic recrystallization temperatures. Roll compression in ARB affects the microstructure and mechanical properties of the composite material, where rolling compression can produce the application of simple forces sequentially evenly on the compressed workpiece. With the addition of Al2O3 and B4C reinforcement in the ARB process, it is expected that the mechanical properties will increase significantly. Composite AA1070 or Al2O3 produces an average hardness: 43.36 BHN, using B4C reinforcement increased 53.50 BHN with AA17075 with Al2O3 reinforcement the hardness was 87.20, with B4C increased significantly by 105.2 BHN. This study compares Al2O3 and B4C as reinforcement on an application in metal matrix composites (MMC). Characteristics compared and comparison of types of AA1070 or AA7075 matrix in their suitability between the use of matrix and reinforcement processed by ARB. Teknologi pengerjaan logam saat ini berkembang pesat, terutama pengolahan bahan-bahan komposit logam. Proses terjadi di mana strain plastik ultra-besar dimasukkan ke dalam perangkat untuk menciptakan logam yang berbutir ultra-halus merupakan metode terbaru untuk menghasilkan logam dengan kekuatan tinggi, metode ini dinamakan dengan accumulative roll bonding (ARB). Temperatur operasional yang ideal yang digunakan pada proses ARB adalah penggunaan temperatur dinamik rekristaslisasi, kompresi roll pada ARB memiliki efek pada struktur mikro dan sifat mekanik dari bahan komposit yang mana kompresi bergulir mampu menghasilkan penerapan gaya-gaya sederhana secara berurutan secara merata pada benda kerja yang mengalami kompresi. Penambahan penguat Al2O3 dan B4C pada proses ARB, terjadi peningkatan secara signifikan. Komposit AA1070/Al2O3 menghasilkan kekerasan rata-rata 43.36 BHN, menggunakan penguat B4C meningkat 53.50 BHN dengan AA7075 berpenguat Al2O3 kekerasan sebesar 87.20, dengan B4C meningkat signifikan sebesar 105.2 BHN. Penelitian ini membandingkan penggunaan Al2O3 dan B4C sebagai penguat dalam penerapanya sebagai penguat dalam kompoisit bermatrik logam. Karakteristik dibandingkan serta pembanding jenis matriks AA1070/AA7075 dalam kesesuaiannya antara penggunaan matriks terhadap penguat yang diproses oleh ARB.